Variation among strains of Borrelia burgdorferi in host tissue abundance and lifetime transmission determine the population strain structure in nature - Zinck, Christopher B; Raveendram Thampy, Prasobh; Uhlemann, Eva-Maria E; Adam, Hesham; Wachter, Jenny; Suchan, Danae; Cameron, Andrew D S; Rego, Ryan O M; Brisson, Dustin; Bouchard, Catherine; Ogden, Nicholas H; Voordouw, Maarten J (PLoS pathogens, 2023)
Pathogen life history theory assumes a positive relationship between pathogen load in host tissues and pathogen transmission. Empirical evidence for this relationship is surprisingly rare due to the difficulty of measuring transmission for many pathogens. The comparative method, where a common host is experimentally infected with a set of pathogen strains, is a powerful approach for investigating the relationships between pathogen load and transmission. The validity of such experimental estimates of strain-specific transmission is greatly enhanced if they can predict the pathogen population strain structure in nature. Borrelia burgdorferi is a multi-strain, tick-borne spirochete that causes Lyme disease in North America. This study used 11 field-collected strains of B. burgdorferi, a rodent host (Mus musculus, C3H/HeJ) and its tick vector (Ixodes scapularis) to determine the relationship between pathogen load in host tissues and lifetime host-to-tick transmission (HTT). Mice were experimentally infected via tick bite with 1 of 11 strains. Lifetime HTT was measured by infesting mice with I. scapularis larval ticks on 3 separate occasions. The prevalence and abundance of the strains in the mouse tissues and the ticks were determined by qPCR. We used published databases to obtain estimates of the frequencies of these strains in wild I. scapularis tick populations. Spirochete loads in ticks and lifetime HTT varied significantly among the 11 strains of B. burgdorferi. Strains with higher spirochete loads in the host tissues were more likely to infect feeding larval ticks, which molted into nymphal ticks that had a higher probability of B. burgdorferi infection (i.e., higher HTT). Our laboratory-based estimates of lifetime HTT were predictive of the frequencies of these strains in wild I. scapularis populations. For B. burgdorferi, the strains that establish high abundance in host tissues and that have high lifetime transmission are the strains that are most common in nature.
Keywords: Borrelia burgdorferi; myši; larva; Larva; myši inbrední C3H; klíště; Lyme Disease; zvířata; Mice; Mice, Inbred C3H; Ixodes; lymeská nemoc; Animals